ABOUT MIKHAIL S. GREENBERG - T. F. Yashchuk (Правоприменение, 2018)
The introductory article of the issue – the obituary – is devoted to the outstanding Soviet and Russian lawyer – professor Mikhail S. Greenberg. The author dwells on the main mile-stones of M.S. Greenberg's scientific biography: from studying at Leningrad State University to conferring the title "Honoured Lawyer of the Russian Federation" during his work in Omsk State University, highlights the main provisions of his scientific works, characterizes the personal qualities of M.S. Greenberg.